Examining Endothelial Function and Platelet Reactivity in Patients with Depression before and after SSRI Therapy - Dawood, Tye; Barton, David A.; Lambert, Elisabeth A.; Eikelis, Nina; Lambert, Gavin W. (Frontiers in Psychiatry, 2016)
While it is recognised that patients with major depressive disorder (MDD) are at increased risk of developing cardiovascular disease (CVD) the mechanisms responsible remain unknown. Endothelial dysfunction is one of the first signs of CVD. Using two techniques, flow mediated dilatation in response to reactive hyperaemia and laser Doppler velocimetry with iontophoresis, we examined endothelial function in the forearm before and after SSRI treatment in 31 patients with MDD. Measurement of intercellular adhesion molecule-1 (ICAM-1), vascular cell adhesion molecule-1, soluble P-selectin and noradrenaline in plasma was also performed. Prior to treatment, markers of endothelial and vascular function and platelet reactivity were within the normal range. Following SSRI therapy (95 ± 5 days) symptoms of depression were reduced (paired difference between pre and post treatment Hamilton rating -18 ± 1, P<0.001) with 19 patients recovered and 4 remitted. There occurred no significant change in markers of endothelial or vascular function following SSRI therapy. The improvement in Hamilton depression rating in response to therapy could be independently predicted by the baseline arterial plasma noradrenaline concentration (r2 = 0.36, P=0.003). In this cohort of patients with MDD SSRI therapy did not influence endothelial function or markers of vascular or platelet reactivity. Patient response to SSRI therapy could be predicted by the initial circulating level of noradrenaline, with noradrenaline levels being lower in responders.